On the glacial-interglacial variability of the Asian monsoon in speleothem δ(18)O records - Liu, G. (Sci Adv, 2020)
While Asian monsoon (AM) changes have been clearly captured in Chinese speleothem oxygen isotope (δ(18)O) records, the lack of glacial-interglacial variability in the records remains puzzling. Here, we report speleothem δ(18)O records from three locations along the trajectory of the Indian summer monsoon (ISM), a major branch of the AM, and characterize AM rainfall over the past 180,000 years. We have found that the records close to the monsoon moisture source show large glacial-interglacial variability, which then decreases landward. These changes likely reflect a stronger oxygen isotope fractionation associated with progressive rainout of AM moisture during glacial periods, possibly due to a larger temperature gradient and suppressed plant transpiration. We term this effect, which counteracts the forcing of glacial boundary conditions, the moisture transport pathway effect.